Changes in treatment pattern and costs in advanced hepatocellular carcinoma (HCC). (2nd January 2022) - Muszbek, Noemi; Evans, Rachel; Remak, Edit; Brennan, Victoria K; Colaone, Fabien; Shergill, Suki; Ross, Paul; Mullan, Damian
ABSTRACT: Introduction: While essential for cost-effectiveness analyses, there are no current resource use and cost data available for advanced hepatocellular carcinoma (HCC) and selective internal radiation therapy (SIRT). The study aims to assess current resource use and costs in HCC and for SIRT compared to historical survey data. Areas covered: To address this data gap, resource use was elicited via surveys and interviews with medical professionals experienced with HCC and SIRT in the United Kingdom. Unit costs were from publicly available databases. Resource use and costs were estimated and compared to prior surveys. Expert opinion: From eleven responses, pre-progression costs for SIRT and systemic therapy were £256.77 and £292.27/month, respectively. One-off progression and post-progression costs were £209.98 and £522.84/month. Monthly costs were 54%-79% lower than in previous surveys, due to reduction in hospitalizations and funded social care. Furthermore, substantial differences in resource use associated with SIRT between clinical practice and clinical trials were found. In conclusion, increased availability and familiarity with systemic treatments has led to important changes in HCC care and SIRT administration. The uncertainty from the use of expert opinion and the limited number of hospitals with SIRT experience can be addressed with future research using large databases, registries.